2017
DOI: 10.4314/tjpr.v16i1.26
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and <i>in vivo</i> anti-hyperlipidemic activity of novel n-benzoylphenyl-2-furamide derivatives in Wistar rats

Abstract: Purpose: To synthesize and evaluate the anti-hyperlipidemic activity of a novel series of N-(benzoylphenyl)-2-furamides

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 21 publications
2
13
0
Order By: Relevance
“…As reported in the literature, the maximum plasma TC and TG levels were reached after 20 h. of Triton WR-1339 treatment followed by a decline to the standard values. In our study, the results of tested compounds were analyzed after 18 h. of treatment and Triton WR-1339 model gave similar pattern in lipid profile changes compared to published data [21][22][23] ( Table 1).…”
Section: Discussionsupporting
confidence: 70%
“…As reported in the literature, the maximum plasma TC and TG levels were reached after 20 h. of Triton WR-1339 treatment followed by a decline to the standard values. In our study, the results of tested compounds were analyzed after 18 h. of treatment and Triton WR-1339 model gave similar pattern in lipid profile changes compared to published data [21][22][23] ( Table 1).…”
Section: Discussionsupporting
confidence: 70%
“…Epidemiological studies have demonstrated that hyperlipidaemia is the most prevalent indicator of susceptibility to atherosclerosis and coronary heart diseases (CHD). Therefore, decreasing plasma lipids play a major role in the treatment and prevention of CHD ( 6 ). Furthermore, hyperlipidaemia and hypercholesterolemia are not only secondary metabolic dysregulations associated with diabetes but also represent increased risk factors for its development ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…The side effects of statins and fibrates are well documented ( 4 , 5 ). For this reason, many studies have been conducted to evaluate the potential lipid-lowering activity of synthetic and natural compounds ( 6 ). It has been suggested that herbal remedies are among the best existing alternative therapies and have been used since ancient times ( 7 ) and they have contributed to the development of important drugs used currently in modern medicine ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, in 2017, they further studied the antihyperlipidemic activities of a few more furamide derivatives containing benzophenone. 112 Compound 76 was found to be the most active. The observations of the authors suggested that the presence of a lipophilic moiety (benzophenone), a carboxamide linkage and a furan ring (which can form hydrogen bonds) are three important requirements for the activity of the synthesized molecules.…”
Section: Antihyperlipidemic Activitymentioning
confidence: 95%